Analysis of Language Style in the Novel Cinta di Dalam Gelas by Andrea Hirata - Lilis Mufarida; Aghnaz Zida Tanaffasha; Fido Dio Aji Firmansyah; Handika Dewa Tengku Firmansyah (Faculty of Languages and Arts, Universitas Negeri Padang, 2022)
This study aims to explain the function of language style based on the direct and indirect meaning found in the novel entitled Cinta di Dalam Gelas by Andrea Hirata. Analysis of language style is chosen to find out the author's characteristics and understand why the author tends to use certain words or expressions in their literary works. The research method used in the study is a type of descriptive-qualitative with stylistic approach. The data collection used is reading the text of Cinta di Dalam Gelas novel repeatedly, then writing evidence in the novel containing the use of language style on the data source. The technique of analyzing data using by finding the data, reducing data, displaying data, analyzing data according to the types of language style, then describing the result of the finding data providing statements from the theory that used. The research finding of this study shows that language style based on the direct and indirect meaning found consists of two kinds, namely rhetorical language style and figurative language style. Rhetorical languages style is composed of Alliteration, Assonance, Rhetoric, Pleonasm, Paradox, Hyperbole, and Litotes. Meanwhile, the figurative language style is crafted of Association, Metaphor, Metonymy, Irony, and Sarcasm.